2015
DOI: 10.1164/rccm.201410-1924oc
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Clean Fuels and Technologies on School Buses. Pollution and Health Impacts in Children

Abstract: Rationale: More than 25 million American children breathe polluted air on diesel school buses. Emission reduction policies exist, but the health impacts to individual children have not been evaluated.Methods: Using a natural experiment, we characterized the exposures and health of 275 school bus riders before, during, and after the adoption of clean technologies and fuels between 2005 and 2009. Air pollution was measured during 597 trips on 188 school buses. Repeated measures of exhaled nitric oxide (FE NO ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 61 publications
3
27
1
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) reported that exposure to diesel exhaust can cause lung cancer (IARC, 2012). Adar et al (2015) surveyed more than 25 million children and concluded that a disproportionate number of cases of respiratory disease were caused by breathing polluted air from diesel school buses. Moreover, nearly 34 % of element carbon (EC) emissions, a major contributor to current global warming and poor human health, originates from off-road diesel vehicle emissions in the United States (USEPA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) reported that exposure to diesel exhaust can cause lung cancer (IARC, 2012). Adar et al (2015) surveyed more than 25 million children and concluded that a disproportionate number of cases of respiratory disease were caused by breathing polluted air from diesel school buses. Moreover, nearly 34 % of element carbon (EC) emissions, a major contributor to current global warming and poor human health, originates from off-road diesel vehicle emissions in the United States (USEPA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…10 Air pollution is a known trigger of chronic obstructive pulmonary disease (COPD) 11 and has informed the establishment of air quality standards in many countries. 12 13 The broad legislative framework for air quality assessment in populated areas was put in place by the European Union Directive on Air Quality 2008/50/ EC. 14 This framework recommended guideline limits for pollutants that have been identified to be injurious to the health of the public, including the environment and the built infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Asmi et al [28] reported higher concentrations of PM 2.5 inside older buses than inside new buses related to differences in bus-to-bus emissions, which could explain the difference reported here. The lower exposure observed in private cars relative to public transport could be due to tailpipe diesel exhaust recirculating to the cabin, which was observed in the California school bus program [29]. Overall, the residuals estimated for the trolleybus, CC and HEC confirmed a lower exposure than that estimated for the other modes of transport evaluated here.…”
Section: Personal Exposure To Pm 25 In the Mcmamentioning
confidence: 44%